Clinical ophthalmology made easy - Abraham, Anina; Senthil, Sirisha (Panamá : Jaypee Brothers Medical Publishers, 2013)
The second edition of Clinical Ophthalmology Made Easy brings postgraduates and residents fully up to date with the most recent advances and developments in the field. Beginning with a chapter on patient evaluation, each of the following chapters is dedicated to a different part of the eye and covers the etiology, pathology, clinical features and management of diseases and disorders that may be encountered. Presented in a practical, easy to follow format, this comprehensive guide includes tables, flow charts, images and illustrations to assist learning. Key points * New edition for postgraduates presenting latest developments in ophthalmology * Covers diseases and disorders in all parts of the eye * Practical, easy to follow format, with tables and illustrations * Previous edition published in 2009
Patient Evaluation Glaucoma Retina Uvea Cornea Conjunctiva Sclera Pediatrics and Squint Neuro-ophthalmology Oculoplasty Lens Trauma Systemic Diseases
Título en inglés
Keywords: OFTALMOLOGÍA; ENFERMEDADES OCULARES